Necesidades Con Relación A La Actividad Física Y El Deporte En La Población Interna Del Hogar San Juan Bosco Y El Amparo De Niños Juan XXIII (2016)
In this work they will find research on the needs they may have children who are part of the child care centers "Amparo de niños Juan XXIII y el Hogar San Juan Bosco" This research aimed to identify the needs in relation to physical activity and sport that have internal children of Amparo de niños Juan XXIII y el Hogar San Juan Bosco and performed with male children in boarding mode households. The sample project consists of a group of 28 children between 8 and 12 years old, where 12 children were part of Amparo de niños Juan XXIII and the other 16 children belonged to Hogar San Juan Bosco. This research was conducted under a quantitative approach and was an exploratory scope with regard to the information collected, although an interpretative intention in developing the analysis of the results is developed. On the other hand, the study is cross-sectional because the surveys were conducted at a single time during the work. To conclude, it has been found that indeed in this population in a state of breach certain needs related to sports and physical activity, mainly related needs aspect of membership that have been deployed in the analysis of the results appear.